Gambaran Histopatologi Kulit Ikan Kerapu Cantang (Epinephelus fuscoguttatus x Epinephelus lanceolatus) yang Terinfestasi Zeylanicobdella arugamensis Setelah Perendaman Menggunakan Perasan Daun Pepaya (Carica papaya) - Putra, Bernathdo Mahendra Robbi; Mahasri, Gunanti; Sulmartiwi, Laksmi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Increasing cultivation activities and intensifying ponds has the potential to give rise to problems, namely increasing cases of disease in grouper fish, namely Zeylanicobdella, causing mass deaths of up to 100%. This study aims to analyze the histopathological picture of grouper skin infested with Zeylanicobdella arugamensis after administering papaya leaf juice with different soaking times and concentrations of papaya leaf juice. The method used was experimental Completely Randomized Design (CRD) with a factorial pattern consisting of two factors, namely factor A, different concentrations of papaya leaf juice consisting of 0% (A1), 0.1% (A2), 0.3% (A3) , and 0.5% (A4), as well as factor B for grouper rearing time consisting of the 0th minute (B1), 60th minute (B2), and 120th minute (B3) with five repetitions. The results of the study showed that the soaking time of papaya leaf juice in grouper fish had an effect on reducing the degree of Zeylanicobdella infestation, there were changes in the histopathological picture and water quality values before and after soaking. Treatments A2, A3, and A4 experienced a decrease in the degree of ectoparasite infestation at 60 and 120 minutes of immersion. The histopathological scoring values for treatments A2, A3, and A4 decreased at 60 and 120 minutes of maintenance. The best treatment combination was 0, 3% and soaking time at 120 minutes. In conclusion, giving papaya leaf juice with a soaking time of 120 minutes with a concentration of 0.3% can reduce the degree of infestation and the histopathological scoring value of Zeylanicobdella in grouper fish.